EKOLEKSIKON KEMARITIMAN SEBAGAI MANIFESTASI PENGETAHUAN EKOLOGIS ORANG PULO DI PULAU PANGGANG, DKI JAKARTA - Sigit Widiatmoko; NFN Krisanjaya; Nur Sekhudin (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2023)
This study aims to describe the form of lingual units and the meaning of the maritime ecolexicon of orang Pulo in Panggang Island, Jakarta. This study uses a qualitative approach. Data collection was carried out using literature study techniques by reading various literature, direct observation to Panggang Island, and interviewing local community leaders. Based on the results of data analysis, there were 68 maritime ecolexicon with lingual units in the form of 29 monomorphemic ecolexicons, 12 polymorphemic ecolexicons formed through reduplication and compounding processes, and 27 ecolexicon phrases. The meaning of the ecolexicon is categorized as fauna, flora, topography, and climate. The meaning of the ecolexicon in the category of fauna refers to fish, squid, crabs, and shell. The meaning of the ecolexicon in the category of flora refers to land plants and sea plants. The classification of biotic diversity (flora and fauna) is carried out based on traditional taxonomy. Ecolexicon meanings were also found in the topographical category referring to land and sea. The meaning of the ecolexicon in the category of climate refers to winds and ocean currents. All ecolexicons are manifestations of the ecological knowledge of orang Pulo which are obtained from experience, inheritance, and interactions with people outside the orang Pulo.Penelitian ini bertujuan untuk mendeskripsikan bentuk satuan lingual dan makna dari ekoleksikon kemaritiman orang Pulo di Pulau Panggang, Jakarta. Penelitian ini menggunakan pendekatan kualitatif. Pengumpulan data dilakukan melalui teknik studi pustaka dengan membaca berbagai literatur, observasi langsung ke Pulau Panggang, dan wawancara tokoh masyarakat setempat. Berdasarkan hasil analisis data, terdapat 68 ekoleksikon kemaritiman terdiri atas satuan lingual berbentuk monomorfemis sebanyak 29 ekoleksikon, polimorfemis sejumlah 12 ekoleksikon yang dibentuk melalui proses reduplikasi dan pemajemukan, dan frasa sebanyak 27 ekoleksikon. Berdasarkan tinjauan makna, ekoleksikon tersebut berkategori fauna, flora, rupabumi, dan iklim. Makna ekoleksikon berkategori fauna mengacu pada ikan, cumi-cumi, kepiting, serta kerang. Makna ekoleksikon berkategori flora mengacu pada tanaman darat serta tanaman laut. Pengklasifikasian ragam biotik (flora dan fauna) tersebut dilakukan berdasarkan taksonomi kerakyatan yang diperoleh secara tradisional. Makna ekoleksikon pun ditemukan berkategori rupabumi yang mengacu pada daratan dan lautan. Makna ekoleksikon berkategori iklim mengacu pada angin dan arus laut. Semua ekoleksikon merupakan manisfestasi pengetahuan ekologis orang Pulo yang diperoleh dari pengalaman, pewarisan, dan interaksi dengan masyarakat luar Pulo.